2023
DOI: 10.3389/fonc.2022.960944
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic performance of radiomics-based MRI in predicting microvascular invasion in hepatocellular carcinoma: A meta-analysis

Abstract: ObjectiveThe aim of this study was to assess the diagnostic performance of radiomics-based MRI in predicting microvascular invasion (MVI) in hepatocellular carcinoma (HCC).MethodThe databases of PubMed, Cochrane library, Embase, Web of Science, Ovid MEDLINE, Springer, and Science Direct were searched for original studies from their inception to 20 August 2022. The quality of each study included was assessed according to the Quality Assessment of Diagnostic Accuracy Studies 2 and the radiomics quality score. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[10,11] Furthermore, the majority of these studies were conducted in single-center settings, lacking external validation. [12,13]…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Furthermore, the majority of these studies were conducted in single-center settings, lacking external validation. [12,13]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a radiomics nomogram developed by Zhang et al 4 to predict HCC recurrence combined with traditional clinical radiology risk factors performed better than conventional nomograms and demonstrated the importance of MRI radiomics. A meta-analysis 27 of 15 studies involving 981 patients indicates that MRI radiomics holds high accuracy in predicting MVI of HCC and can be considered a non-invasive method for evaluating the presence of MVI in HCC patients. Zhang et al 28 assessed MRI scans of 136 primary liver cancer patients and found that radiomics characteristics were independently associated with OS of distinct pathological types.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning algorithms process these features to generate predictive models that contribute to the diagnosis, treatment, and prognosis assessment of HCC [11] , [12] . Prior investigations have demonstrated the practical value of radiomic features extracted from MR or CT images for predicting HCC recurrence and survival [7] , [13] , [14] , [15] . However, there has been little research on its application in predicting EHM in HCC patients treated with TACE.…”
Section: Introductionmentioning
confidence: 99%